Addiction to Electronic Games Among teenagers and Its Role in the Emergence of Certain Psychological and Educational Disorders (Revue El-Wahat pour les Recherches et les Etudes, 2025)
Video Games Are A Double-Edged Sword. On The Positive Side, They Contribute To The Intellectual Development Of Teenagers And Support Their Psychological And Emotional Growth. However, Their Negative Impact Has Increasingly Overshadowed These Benefits, Especially In Cases Of Addiction. Since Adolescence Is A Critical Stage Of Development, Excessive Gaming Can Lead To Severe Consequences Affecting The Physical, Psychological, Cognitive, Social, Religious, And Cultural Aspects Of An Individual. Moreover, It May Result In More Serious Complications, Including Various Psychological Disorders. Understanding These Effects And Consequences Helps In Assessing The Severity Of The Issue, Enabling Us To Develop Preventive And Therapeutic Strategies To Address It. This Study Aims To Shed Light On These Aspects.Keywords: Video Game Addiction , Teenagers , Psychological And Educational Disorders